2005
DOI: 10.1590/s0101-81752005000100015
|View full text |Cite
|
Sign up to set email alerts
|

Habitat structure and small mammals abundances in one semiarid landscape in the Brazilian Caatinga

Abstract: Studies conducted under a major project sponsored by the Brazilian Academy of Sciences in the 1970's concluded that the small mammal fauna of the semiarid Caatinga region of Brazil is impoverished and highly restricted to mesic granite outcroppings due to the lack of water conserving physiological capabilities in its species. This work focuses the abundance of small mammals in five typical Caatinga habitats. Indirect gradient analysis shows that three theoretical environmental variables explain most of the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 10 publications
2
8
0
6
Order By: Relevance
“…Thrichomys laurentius, D. albiventris, and G. agilis were the most abundant species in non-volant communities, as detected in previous studies in other Caatinga localities (e.g., Freitas et al 2005). Thrichomys laurentius is a common rodent species, with herbivorous and semiterrestrial habits (Reis et al 2011).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Thrichomys laurentius, D. albiventris, and G. agilis were the most abundant species in non-volant communities, as detected in previous studies in other Caatinga localities (e.g., Freitas et al 2005). Thrichomys laurentius is a common rodent species, with herbivorous and semiterrestrial habits (Reis et al 2011).…”
Section: Discussionsupporting
confidence: 71%
“…The low capture success and species richness compared to that frequently observed in other biomes were the common pattern found for non-volant small mammals communities in other areas within the Caatinga (e.g., Freitas et al 2005;Bezerra et al 2014). Freitas et al (2005) and Bezerra et al (2014) recorded six and eight species of non-volant small mammals in a global capture success of 0.56% (total sampling effort = 8,952 trapnights) and 1.54-0.27% (total sampling effort = 5,369 trap-nights and 2,880 bucket-nights), respectively.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In fact, this climatic variable must be taken into consideration, especially in environments with unpredictable and erratic rainfalls, where months or even years of drought may occur (Nimer 1972). During the rainy season, few individuals were collected, a result similar to that found in a caatinga of Bahia state, where twice more individuals were captured during the dry season (Freitas et al 2005). It is probably due to the availability of abundant resources like fruits and leaves (Lima 2007), which facilitated foraging in smaller areas, with consequent fewer encounters with traps, and/or making baits less appealing.…”
Section: Comparison Of Sampling Efforts and Species Richnesssupporting
confidence: 65%
“…Some studies have shown that for the small mammals, sympatry may be made possible by distinct periods of activity (Graipel et al 2003a, Oliveira-Santos et al 2008, food requirements (Campos et al 2001, Cáceres et al 2002 and the differential use of vertical space in forests (Vieira andMonteiro-Filho 2003, OliveiraSantos et al 2008). However, most studies suggest that the selection of distinct habitats is the most important mechanism that allows species of small mammals to coexist (Price 1978, Dalmagro and Vieira 2005, Freitas et al 2005. Therefore, analyses of space use patterns are a central requirement to infer competitive relationships and mechanisms of coexistence among species of this group (Cunha and Vieira 2004).…”
Section: Introductionmentioning
confidence: 99%